2016
DOI: 10.1038/cddis.2016.269
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly cycling Lgr5+ stem cells are exquisitely sensitive to extrinsic dietary factors that modulate colon cancer risk

Abstract: The majority of colon tumors are driven by aberrant Wnt signaling in intestinal stem cells, which mediates an efficient route toward initiating intestinal cancer. Natural lipophilic polyphenols and long-chain polyunsaturated fatty acids (PUFAs) generally suppress Wnt- and NF-κB- (nuclear factor-κ light-chain enhancer of activated B-cell) related pathways. However, the effects of these extrinsic agents on colonic leucine-rich repeat-containing G-protein-coupled receptor 5-positive (Lgr5+) stem cells, the cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…Recent data from one of these phase IIa clinical trials indicates that consumption of curcumin at 4 g per day for 30 days significantly (40%) reduces the number of aberrant crypt foci (ACF) in a CRC model [304] and in men and women [305]. More recently, our laboratory examined the effect of n-3 PUFA and curcumin in a mouse colorectal cancer initiation model and found that these agents when combined synergistically reduced (75%) the number of ACF in a mouse CRC model [28]. Importantly, several studies have confirmed that curcumin is well tolerated and that the effect is potentially mediated by curcumin delivered to the target tissue, i.e., it is directly incorporated into the intestinal mucosa [28, 305, 306].…”
Section: Cancer Chemoprevention By Membrane-targeted Dietary Bioactivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data from one of these phase IIa clinical trials indicates that consumption of curcumin at 4 g per day for 30 days significantly (40%) reduces the number of aberrant crypt foci (ACF) in a CRC model [304] and in men and women [305]. More recently, our laboratory examined the effect of n-3 PUFA and curcumin in a mouse colorectal cancer initiation model and found that these agents when combined synergistically reduced (75%) the number of ACF in a mouse CRC model [28]. Importantly, several studies have confirmed that curcumin is well tolerated and that the effect is potentially mediated by curcumin delivered to the target tissue, i.e., it is directly incorporated into the intestinal mucosa [28, 305, 306].…”
Section: Cancer Chemoprevention By Membrane-targeted Dietary Bioactivesmentioning
confidence: 99%
“…This suggests that select MTDBs could reduce cancer risk by attenuating oncogenic protein activity by modulating the membrane organization of essential proteins and lipids. Thus, MTDBs could potentially serve as chemoprotective agents for cancer therapy [2830]. In this review, we describe the importance of the plasma membrane as a central cellular hub that integrates numerous cues to orchestrate the modulation of various signaling networks, which can become hyperactivated, resulting in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…n-3 PUFA and curcumin paradoxically increase injury scores in an inflamed animal model [52], while the same n-3 PUFA dose has beneficial effects in a colon cancer model [67]. Along these lines, it has been demonstrated that fish oil feeding increases colon inflammation in a genetically susceptible mouse model [68], while exhibiting a chemo-protective tumor suppressing effect in an inflamed colon cancer animal model [69].…”
Section: Introductionmentioning
confidence: 99%
“…Adding to the complexity, recent evidence indicates that multiple stem cell hierarchies exist in the intestine and that plasticity within stem cell hierarchies mediates cellular fate in response to extrinsic factors such as nutrition, inflammation, and physical stress signals [5458]. Interestingly, a role for diet in the regulation of intestinal stem cells has been reported [5962]. …”
Section: Host and Microbe-associated Alterations As Contributors Tmentioning
confidence: 99%
“…For example, combining the dietary polyphenol curcumin with fish oil, rich in n-3 polyunsaturated fatty acids, was recently shown to reduce nuclear β -catenin in aberrant crypt foci in mice exposed to AOM [62]. Furthermore, this combination of dietary bioactives was shown to synergistically increase targeted apoptosis in Lgr5 + stem cells.…”
Section: Dietary Mediators Of Colon Tumorigenesismentioning
confidence: 99%